Clicks and checks: investigating the association between internet usage frequency and women's uptake of clinical breast examination in Ghana - Joshua Okyere; Castro Ayebeng; Kwamena Sekyi Dickson (BMC, 2024)
Abstract Background In resource-constrained settings, availability and access to mammography is a challenge. As such, the World Health Organization (WHO) recommends clinical breast examination (CBE) for women in such settings. Yet, CBE uptake remains low. We, therefore, aimed to contribute to the discourse on factors that influence women's screening practice by investigating the association between the frequency of internet use and women's uptake of CBE in Ghana. Methods This study was based on data from 15,013 women who participated in the 2022 Ghana demographic and health survey. We performed descriptive analysis, computed Pearson's chi-square test, and fitted multivariable logistic regression models. The findings from the regression model were presented in adjusted odds ratio (AOR) at a 95% confidence interval. Results Only 18.39% of women 15-49 years had their breasts examined by a healthcare provider. About 38.22% of the total sample often used the internet. Compared to women who did not use the internet at all, those who often used it had twice the odds of getting screened (COR = 2.86; 95%CI: 2.62-3.13). The odds of CBE uptake remained significantly higher among those who often used the internet (AOR = 1.26; 95%CI: 1.12-1.43) even after adjusting for the covariates. Conclusion We conclude that CBE uptake is significantly high among women who frequently use the internet. This association persists even when considering other influential factors such as age, education level, marital status, and socioeconomic status. As such, it is imperative for the Ministry of Health in collaboration with the Ghana Health Service to recognize the potential of digital health interventions, including online health education campaigns and telehealth services, in reaching and engaging women to get their breast examined by a healthcare provider.